THE INFLUENCE OF THE INTENSITY OF GADGET USE ON THE SPIRITUAL OF EARLY CHILDREN (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
This research is motivated by the existing problems, namely, the Era of Globalization in technological development. Gadget technology that appears at this time is unsuitable for human personality, especially in early childhood, where this gadget means a mini-sized electronic or digital device with special uses. This research aims to examine the influence of the intensity of gadget use on spirituality in early childhood kids. The results of the study show that the positive impact obtained from the intensity of using gadgets when used properly is that it can stimulate children's creativity, especially if it is balanced with work. It can train children to think more critically and make it easier for them to communicate more intensely. Children can become smarter in choosing a variety of information.